Chitosan/carrageenan nanoparticles: effect of cross-linking with tripolyphosphate - Rodrigues, Susana (2012)
Chitosan/carrageenan/tripolyphosphate nanoparticles were prepared by polyelectrolyte complexation/ionic gelation, the latter compound acting as cross-linker. The incorporation of the three components in the nanoparticle matrix was assessed by analytical techniques (FTIR, XPS and TOF-SIMS). Using chitosan/carrageenan nanoparticles as control, the effect of the cross-linker in the particles properties was studied. A decrease in size (from 450-500 nm to 150-300 nm) and in zeta potential (from +75 - +85 mV to +50 - +60 mV), and an increase in production yield (from 15-20% to 25-35%), and in stability (from one week to up to 9 months) were observed. Also, a correlation between positive to negative charge ratios in the formulations and the above characteristics was established. The small size and high positive surface charge make the developed chitosan/carrageenan/tripolyphosphate nanoparticles potential tools for an application in mucosal delivery of macromolecules.